Thriving in turbulent times the interplay of organizational learning capability & employee work role performance : the mediating role of organizational resilience - Kavurmacıoğlu, Refakat Gülten (My University, 2022)
The aim of this study is to find which organizations will be able to overcome – and even evolve – in the turbulent market environments. Building resilience in organizations is crucial to keep their competitive position in the face of crises and uncertainty. This study uniquely proposes a practical approach to Organizational resilience by building a model for its connection with Organizational Learning Capability. The impact of Organizational Learning Capability on organizational resilience and employee performance are analyzed. Adaptivity and proactivity are crucial dimensions in facing chaotic situations; and an employee performance model including them is utilized. Survey of 129 was conducted in private sector companies in Ankara, Istanbul. The result indicates that organizational learning capability makes a positive contribution on both employee work role performance and organizational resilience and organizational resilience itself mediates this relationship. As long as companies invest in learning, they enhance their resilience and increase employee performance.

Bu araştırmanın amacı hangi firmaların çalkantılı zamanların üstesinden gelebileceklerini hatta büyüyebileceklerini tespit edebilmektir. Kurumsal yılmazlık, belirsizlik ve kriz dönemlerinde rekabetçi konumu korumak için çok önemlidir. Bu çalışma henüz kavramsal tartışmaları süren kurumsal yılmazlık için, örgütsel öğrenme kabiliyeti arasında bir bağlantı oluşturarak, özgün, uygulamaya dönük bir yaklaşım önerir. Örgütsel öğrenme kabiliyetinin örgütsel yılmazlık üzerine ve çalışan performansı üzerine etkisi incelenir. Kaos ortamındaki belirsizlik koşullarını dikkate alan ve adaptasyon, proaktiflik boyutlarını da içeren bir performans ölçme modeli kullanılarak önermenin sonuçları ölçülür. Özel sektör firmalarında 129 adet anket uygulanarak ölçüm yapılmıştır. Sonuçlar örgütsel öğrenme kabiliyetinin kurumsal yılmazlığa ve çalışan iş role performansına pozitif katkıda bulunduğunu, kurumsal yılmazlığın, örgütsel öğrenme kabiliyeti ve çalışan iş role performansı arasındaki ilişkide aracı rolü oynadığını desteklemiştir. Bu bulgu öğrenmeye yatırım yapan kurumların, aynı zamanda yılmazlıklarını da geliştirdiklerini ve bunların sonucunda da çalkantılı zamanlarda çalışanların performansını yükseltebildiklerini destekler.
Keywords: Business; Çalışan İş Rol Performansı; Employee Work Role Performance Örgütsel Öğrenme Kapasitesi; İşletme; Organizational Learning Capability; Organizational Resilience; Örgütsel Yılmazlık